Pretreatment of rice straw with combined process using dilute sulfuric acid and aqueous ammonia - Kim, Sung Bong; Lee, Sang Jun; Lee, Ju Hun; Jung, You Ree; Thapa, Laxmi Prasad; Kim, Jun Seok; Um, Youngsoon; Park, Chulhwan; Kim, Seung Wook (BioMed Central, 2013)
Background: Use of lignocellulosic biomass has received attention lately because it can be converted into various versatile chemical compounds by biological processes. In this study, a two-step pretreatment with dilute sulfuric acid and aqueous ammonia was performed efficiently on rice straw to obtain fermentable sugar. The soaking in aqueous ammonia process was also optimized by a statistical method. Results: Response surface methodology was employed. The determination coefficient (R-2) value was found to be 0.9607 and the coefficient of variance was 6.77. The optimal pretreatment conditions were a temperature of 42.75 degrees C, an aqueous ammonia concentration of 20.93%, and a reaction time of 48 h. The optimal enzyme concentration for saccharification was 30 filter paper units. The crystallinity index was approximately 60.23% and the Fourier transform infrared results showed the distinct peaks of glucan. Ethanol production using Saccharomyces cerevisiae K35 was performed to verify whether the glucose saccharified from rice straw was fermentable. Conclusions: The combined pretreatment using dilute sulfuric acid and aqueous ammonia on rice straw efficiently yielded fermentable sugar and achieved almost the same crystallinity index as that of alpha-cellulose.